Efektivitas Isometric Handgrip Exercise dalam Menurunkan Tekanan Darah pada Pasien Hipertensi - Ricky Zainuddin; Paramitha Labdullah (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Hypertension has a significant impact on public health and has become a major health care burden worldwide. One non-pharmacological therapy that can be given to reduce blood pressure in hypertensive patients is Isometric Handgrip Exercise exercise therapy. This therapy has been shown to reduce blood pressure which is almost the same as intense aerobic exercise. This literature review aims to analyze the effects of the application of Isometric Handgrip Exercise in reducing blood pressure in hypertensive patients. Method: This research explores quantitative evidence published in electronic databases such as Pubmed, and Google Scholar. Using a search strategy, we identified 16 articles that were potentially and relevant to the research objectives, and 4 articles were included in the final analysis. Results: We could see a significant effect on systolic and diastolic blood pressure reduction in the group given the Isometric Handgrip Exercise intervention compared with the control group. Conclusion: Research results from several articles in this review literature show that Isometric Handgrip Exercise exercises are proven to be effective in reducing blood pressure in hypertensive patients.